PEMBELAJARAN AL-QUR’AN DENGAN METODE TALAQQI BAGI MINORITAS MUSLIMAH CAMBODIA - Heriadi Heriadi; Katni Katni; Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2021)
Abstract Khleang Village Kroch Chmaar District is a Muslim minority village in Cambodia. The condition Svay of Islam is still very limited in the quantity of Islamic education. Islamic educational institutions are still limited, there is an Islamic Foundation called SEPAMA which has an Islamic educational institution at the elementary school level, as well as being used as Al-Quran learning for Muslim women in Svay Khleang Village.Interestingly, even though they are 50 years old, they are very eager to learn the Koran, even when there is a blackout, they are still present learning to recite the Qur'an, which makes researchers interested in taking this research. The purpose of this research is to describe the implementation of Al-Qur'an learning with the Talaqqi Method for Muslim Women in Svay Khleyang Cambodia Village. To describe the results of the implementation of Al-Qur'an learning with talaqqi method for Muslim women. To describe the supporting and inhibiting factors of the implementation of Al-Qur'an learning with the talaqqi method for Muslimah Kampung Svay Khleang, Kroch Chmaar Cambodia District. This research is a qualitative study, collecting data using interviews, observations, documentation, which all of this is to answer related issues related to the study of Al-Qur'an Learning With the Talaqqi Method for Muslimah. Data analysis uses descriptive qualitative analysis. The findings of this research are: (1) The implementation of Al-Qur'an learning with the talaqqi method for Muslim women begins to read the Surah Al-Fatihah then imitated by mothers and continued reading juz 30 listened and followed, then read juz 29, juz 28, juz 1, juz 2 all listened and then followed by reading continuously until smoothly then another letter continued. Around 50 Muslim women participated, and it was held every Wednesday, Friday and Saturday at 18:30-20.30. (2) The results of the implementation of Al-Qur'an learning for Muslim women have improved very well, starting reading fluently, knowing the length of the short and wrong and there are memorized juz 30, and other selection letters such as Al-Mulk and Al-Waqiah and and pronounce the letters with proper and fluent and fluent reading of the makhroj. (3) Supporting factors for the implementation of Al-Qur'an learning with the talaqqi method for Muslim women, namely the teacher is proficient in reading the Qur'an and is fluent and equipped with adequate facilities and infrastructure. The inhibiting factor is the lack of human resources and a manual of the Qur'an and a reference book for the learning curriculum of the Qur'an. AbstrakKampung Svay Khleang Distrik Kroch Chmaar merupakan kampung minoritas muslim di Cambodia. Kondisi Islam masih sangat terbatas kuantitas pendidikan Islam. Lembaga pendidikan Islam pun masih terbatas, terdapat sebuah Yayasan Islam bernama SEPAMA yang memiliki lembaga pendidikan Islam setingkat sekolah dasar, sekaligus digunakan sebagai pembelajaran Al-Quran bagi Para Muslimah di Kampung Svay Khleang. Menariknya walaupun umur mereka 50 tahun lebih mereka sangat bersemangat belajar al-Quran, bahkan pada waktu mati lampu juga tetap hadir belajar mengaji Al-Qur’an hal ini yang menjadikan peneliti tertarik untuk mengambil penelitian ini. Tujuan Penelitia ini adalah mendeskripsikan implementasi pembelajaran Al-Qur’an dengan Metode Talaqqi bagi Muslimah Kampung Svay Khleyang Cambodia. Untuk mendeskripsikan hasil implementasi pembelajaran Al-Qur’an dengan metode talaqqi bagi muslimah. Untuk mendeskripsikan faktor pendukung dan penghambat implementasi pembelajaran Al-Qur’an dengan metode talaqqi bagi Muslimah Kampung Svay Khleang Distrik Kroch Chmaar Cambodia. Penelitian ini merupakan penelitian kualitatif, pengumpulan datanya menggunakan wawancara, observasi, dokomentasi, yang mana semua ini untuk menjawab terkait permasalahan terkait yang diteliti Implementasi Pembelajaran Al-Qur’an Dengan Metode Talaqqi bagi Muslimah. Analisis data menggunakan analisis diskriptif kualitatif. Hasil temuan peneliti ini adalah: (1) Implementasi pembelajaran Al-Qur’an dengan metode talaqqi bagi muslimah dimulai membaca surat Al-fatihah lalu ditirukan ibu-ibu dan dilanjutkan membaca juz 30 disimak dan diikuti, lalu membaca juz 29, juz 28, juz 1, juz 2 semua menyimak lalu diikuti bacaannya terus menerus hingga lancar baru dilanjut surat yang lain. Diikuti sekitar 50 muslimah, dan dilaksanakan setiap hari rabu, jumat dan sabtu pukul 18.30-20.30. (2) Hasil implementasi pembelajaran Al-Qur’an bagi muslimah mengalami peningkatan yang sangat baik mulai bacaannya lancar, mengetahui panjang pendeknya dan salahnya serta ada yang hafal juz 30, dan surat pilihan lainnya seperti Al-Mulk dan Al-Waqiah dan serta mengucapkan hurufnya dengan tepat serta bacaan makhrojnya fasih dan lancar. (3) Faktor pendukung implementasi pembelajaran Al-Qur’an dengan metode talaqqi bagi muslimah yaitu gurunya mahir dalam membaca Al-Qur’an dan fasih serta dilengkapi sarana dan prasarana yang memadai. Faktor penghambat ialah kurangnya SDM dan buku panduan Al-Qur’an serta buku acuan kurikulum pembelajaran Al-Qur’an yang memadai.